Long‐ and short‐term postseismic gravity changes of megathrust earthquakes from satellite gravimetry. Issue 15 (7th August 2014) - Tanaka, Yusaku; Heki, Kosuke
Abstract Using monthly satellite gravimetry data, we studied time‐variable gravity field after three M9 class earthquakes, the 2004 Sumatra‐Andaman, 2010 Chile (Maule), and 2011 Tohoku‐oki earthquakes. The observations showed that the gravity typically (1) decreases coseismically, (2) continues to decrease for a few months, and (3) increases over a longer period. Therefore, postseismic gravity changes have two components with different time constants and polarities. The mechanisms of short‐ and long‐term postseismic gravity changes are not as clear as coseismic changes at the moment, but might be explained to some extent with afterslip and the Maxwell viscoelasticity, respectively. These two components are difficult to discriminate with surface velocity measurements because the forearc area moves trenchward at both stages. They appear in different polarities in gravity, making satellite gravimetry a unique tool to separate them.